Pengaruh Kemampuan Berpikir Kreatif dan Kepercayaan Diri Siswa yang Mengikuti Organisasi Sekolah Terhadap Hasil Belajar Matematik - Lidyasari; Alimuddin; Nurwati Djam’an (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2017)
This research is ex post facto research aims to know the influence of creative thinking and self confidence of students who follow the organization of the school on the mathematics learning outcomein material opportunities of students of SMA Segeri Pangkep regency. The population of this study is all students of class XI IPA SMA Segeri in the academic year 2016/2017. Sampling using simple random sampling technique.Then got 2 classes as sample. This research only examine student who follow organization of school with number of student follow school organization from 2 classes that is 43 students. The data were collected by using three instruments, namely the test of creative thinking ability, self-confidence questionnaire and test of mathematics learning result. The data is processed using SPSS. The result of descriptive statistics analysis shows that the result of mathematics learning of class XI IPAstudents of SMA Negeri who follow the organization of the school is in the medium category, the ability to think creatively is in good category and very good while for the students' self-confidence is categorized being. The result of inferential analysis shows that there is a mutual influence between the ability of creative thinking and students 'self confidence in the students' mathematics learning outcomes of grade XI IPA SMA Segeri.